The effectiveness of combined Orton-Davis method as distance learning on dyslexia of dyslexic female students in elementary school in Tehran in Covid-19 Pandemic Period - Mohammadi, Shirin; Baseri, Ahmad; Mohammadi Aria, Alireza (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of the present study was to determine the effectiveness of the integrated method of Orton-Davis in the form of distance education on dyslexia of dyslexic female students in elementary school in Tehran. Methods: The research method in this study was semi-experimental and pre-test-post-test design with control group. The statistical population of this study was all the dyslexic primary school girls who attended learning disorders centers in Tehran in 2020-21. To measure the dependent variable of the study, the Nema reading and dyslexia test (Kormi Nouri and Moradi, 2014) was used. In this research, two educational interventions of the integrated Orton-Davis method, which is one of the multi-sensory methods and includes tasks based on directional games, were designed and compiled by Atchershawi (2019) to improve reading skills and reduce dyslexia. Results: The results showed that the combined method of Orton-Davis in the form of distance education on the overall performance of reading (P